Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/c9nr09575f
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven motion of water droplets with directional control on nanostructured surfaces

Abstract: Discrete droplet transport has drawn much interest in a broad range of applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Droplet manipulation in light field can be achieved through photoresponsive materials 99,100,120 and the photothermal effect. 101,121 An et al 99 achieved droplet transport along a predetermined orbit on a surface that could deformed under the light stimulation at an average speed of over 1 cm/s (Figure 11a). The substrate with nanostructures underwent thermal expansion under the action of light, which caused the base to tilt.…”
Section: Strategies Of Droplet Manipulation In a Light Fieldmentioning
confidence: 99%
“…Droplet manipulation in light field can be achieved through photoresponsive materials 99,100,120 and the photothermal effect. 101,121 An et al 99 achieved droplet transport along a predetermined orbit on a surface that could deformed under the light stimulation at an average speed of over 1 cm/s (Figure 11a). The substrate with nanostructures underwent thermal expansion under the action of light, which caused the base to tilt.…”
Section: Strategies Of Droplet Manipulation In a Light Fieldmentioning
confidence: 99%
“…For instance, shorebirds use surface tension to induce transport of millimetric droplets in their beaks; 1,2 in microuidics, [3][4][5] printing, 6,7 and oil-water separation, 8 the microchannel is conducive to achieve directional transport of droplets. Thus far, there have been many techniques to propel droplet motion using an external oscillatory electric eld, 9,10 chemical reaction, 11 vibrating substrates, 12,13 thermal gradients, 14,15 light, 16 and magnetic elds. 17 Lv et al 18 reported a strategy to drive droplets by light-induced asymmetric deformation of the channel wall.…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugal drive [11] is one of many droplet driving methods. Compared with other driving methods, it does not need to rely on external high-precision equipment like surface tension drive [12][13][14]; only a simple motor can drive it. It is also not as sensitive to the physical/chemical properties of liquids as magnetic drive [15], which can be used to drive biological fluids such as blood, urine, and organic solvents.…”
Section: Introductionmentioning
confidence: 99%